An Introduction to Utilizing Community Leaders to Expand Resiliency Efforts Following a Disaster - Lisa Lundy; Jacqueline Aenlle; Ricky W. Telg; Tracy Irani; Angie Lindsey; Ashley Mcleod-Morin; Michaela Kandzer; Phillip Stokes (EDIS, 2021)
In the southeastern United States, many agricultural, vulnerable, and rural communities (AVRCs) must cope with natural disasters regularly. These natural disasters not only harm communities, crops, and livelihoods, but also can negatively impact the mental health of affected individuals, including those living in AVRCs. The purposes of this new 3-page article are to (1) provide tips on identifying specific individuals who could qualify as community leaders and (2) provide details on how partnering with community leaders can be beneficial for mental health communication and outreach. Written by Lisa Lundy, Jacqueline Aenlle, Ricky Telg, Tracy Irani, Angie Lindsey, Ashley Mcleod-Morin, Michaela Kandzer, and Phillip Stokes, and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc383